Shortcoming of ypStage staging system: Lack of differentiation for preoperative treatment - Peizhun Du; Jinzhe Zhou; Pengcheng Liu; Guangjian Huang; Cheng'en Hu (PLoS ONE, 2025)
The eighth edition of the AJCC staging manual initially proposed the ypTNM staging system, which was specifically designed to assess the staging and predict the prognosis of cancer patients undergoing preoperative treatment. Nevertheless, it remains unclear whether this staging system is an accurate predictor of outcomes for cancer patients undergoing different preoperative treatments. The clinical and pathological data of gastric cancer patients who received preoperative treatment and subsequent curved tented gastrostomy were obtained from the Surveillance, Epidemiology, and End Results database. A comparison of survival rates was conducted between patients with the same ypStage staging who received preoperative chemotherapy or chemoradiotherapy, using the Kaplan-Meier method. Additionally, a Cox regression analysis was performed to identify the factors influencing survival following preoperative treatment. A total of 202 patients were included in the study. The results demonstrated a statistically significant difference (p <  0.05) in survival between patients who received preoperative chemoradiotherapy and those who received preoperative chemotherapy in ypStage II or III patients.Cox regression analysis revealed that ypT, ypN and ypStage were associated with OS, but were not independent prognostic factors following gastrectomy. The survival of gastric cancer patients who are classified in the same ypStage stage but who receive disparate preoperative treatments is not analogous. The eighth edition staging system remains in need of further refinement to ensure accurate prediction of prognosis following diverse preoperative therapeutic regimens.